2022
DOI: 10.3389/fmed.2022.982892
|View full text |Cite
|
Sign up to set email alerts
|

Effect of keratometric astigmatism on visual outcomes following small incision lenticule extraction

Abstract: PurposeTo investigate the influence of keratometric astigmatism on visual outcomes following small incision lenticule extraction (SMILE).MethodsEighty eyes undergoing SMILE for myopia correction were classified into two groups based on preoperative keratometric astigmatism: low keratometric astigmatism (LA) and high keratometric astigmatism (HA) groups. Refractive outcomes, vector components, and changes in higher order aberrations (HOAs) were evaluated preoperatively and 6 months postoperatively.ResultsAt the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Some researchers have studied the relationship between the degree of astigmatism and induction of HOA, but no consensus [ 26 28 ]. Zhong et al [ 15 ] observed that there was no significant difference in the induction of tHOA, SA, or CA between high and low astigmatism groups, which is consistent with the findings of Liu et al [ 29 ] and Jun et al [ 27 ] However, Huang et al [ 28 ] confirmed that in eyes with large ablation eccentricity, the values of induced CA and SA were higher in the high astigmatism group than in the low astigmatism group, which was similar to the results of this study. Huang et al further pointed out that for patients with high astigmatism, when the eccentricity of fixation exceeds 0.20 mm, the sensitivity between the significant induction of CA and the eccentric distance after SMILE increased significantly [ 28 ].…”
Section: Discussionsupporting
confidence: 85%
“…Some researchers have studied the relationship between the degree of astigmatism and induction of HOA, but no consensus [ 26 28 ]. Zhong et al [ 15 ] observed that there was no significant difference in the induction of tHOA, SA, or CA between high and low astigmatism groups, which is consistent with the findings of Liu et al [ 29 ] and Jun et al [ 27 ] However, Huang et al [ 28 ] confirmed that in eyes with large ablation eccentricity, the values of induced CA and SA were higher in the high astigmatism group than in the low astigmatism group, which was similar to the results of this study. Huang et al further pointed out that for patients with high astigmatism, when the eccentricity of fixation exceeds 0.20 mm, the sensitivity between the significant induction of CA and the eccentric distance after SMILE increased significantly [ 28 ].…”
Section: Discussionsupporting
confidence: 85%